Architecture of Josef Hoffman in Foreign Historiography of the 1990–2000s - Danilova, Nina L. (Actual Problems of Theory and History of Art, 2025)
The article presents an overview of contemporary researches dedicated to Josef Hoffmann’s work in the context of Austrian architecture of the first quarter of the 20th c. The author focuses on the basic tendencies in historiography, on the description of individual approaches of contemporary researchers involving the related disciplines in studying the architect’s heritage.
Keywords: Josef Hoffmann; Austria; architecture; historiography; Wiener Werksttte